Nutritional status changes in children with malignant solid tumor before and after chemotherapy - Boris Januar; Sri S Nasar; Rulina Suradi; Maria Abdulsalam (Paediatrica Indonesiana, 2005)
Background Although aggressive multimodal treatment programsin childhood cancer have significantly increased survival rates, themorbidity caused by protein energy malnutrition related to therapyis still high.Objective To describe nutritional status changes in children withmalignant solid tumors after 21 days of chemotherapy.Methods A descriptive prospective study with pre- and post-testdesign in children with malignant solid tumors was conducted inthe Department of Child Health, Medical School University of In-donesia/Cipto Mangunkusumo Hospital, Jakarta between Janu-ary and July 2004. Anthropometrics (body weight, BW and mid-upper-arm circumference, MUAC) and serum albumin measure-ments were performed before and after 21 days of chemotherapy.Results Twenty-two children were enrolled in this study. After 21days of chemotherapy, 8 children had decreased BW and 6 chil-dren had decreased MUAC, but 3 children gained weight and hadincreased MUAC. Based on MUAC-for-age, 7 children had de-creased nutritional status. Fifteen children had reduced serum al-bumin levels based on a 10% cut-off point. The number of childrenwho had reduced serum albumin was larger than those who hadreduced BW and MUAC. In the evaluation of average oral foodconsumption during 21 days, 7 out of 16 children could acceptmore than 2/3 portion of served food. All of the children who re-ceived enteral feeding could accept more than 2/3 portion of servedfood.Conclusion There was a decrease of nutritional status, BW,MUAC, and serum albumin in most of the subjects after chemo-therapy. Serum albumin level measurement was the more sensi-tive parameter in determining nutritional status changes. Enteralfeeding seems more appropriate to fulfill nutritional needs than oralfeeding